2006
DOI: 10.1097/01.prs.0000208297.02556.a5
|View full text |Cite
|
Sign up to set email alerts
|

The Free Serratus Anterior Flap and Its Cutaneous Component for Reconstruction of the Face: A Series of 27 Cases

Abstract: The serratus anterior musculocutaneous flap is reliable and particularly well-suited for reconstruction of the face, and has many advantages. The authors speculate that the skin paddle may be vascularized by perforators from the intercostal vessels communicating with the thoracodorsal pedicle through intramuscular choke vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…She recognized intercostal artery perforators reaching the skin, as well as giving branches to Serratus Anterior during their intramuscular course. However, she did not observe any anastomosis between these muscular branches and the Serratus Artery branch [12].…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…She recognized intercostal artery perforators reaching the skin, as well as giving branches to Serratus Anterior during their intramuscular course. However, she did not observe any anastomosis between these muscular branches and the Serratus Artery branch [12].…”
Section: Resultsmentioning
confidence: 85%
“…The studies included in our review, reported 54 successful flaps with a cutaneous component. The flaps were either pedicled or free and were aimed to reconstruct defects in various anatomic areas, most commonly head and neck defects [6], [9], [11], [12], [25],, [26] (Table IV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the GMFT, which represents the gold‐standard for dynamic facial reanimation, the SAFF provides similar muscle bulk and a reliable, long neurovascular pedicle. The option for skin paddles 14 , 15 , 16 , 40 , 41 , 42 , 43 and especially the creation of multiple predictable force vectors represent strong arguments for using the SAFF for immediate dynamic facial reanimation after ablative parotid surgery. Some surgeons even argue against the SAFF because of the need of repositioning after ablative surgery and the supposed significant time delay.…”
Section: Discussionmentioning
confidence: 99%